PENGARUH KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACAE SHOPEE - Mutazam, Zidan Hoerul; Winarso, Widi; Kurniawan, Dody; Komariah, Neng Siti; Anas, Haryudi (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
The rapid growth of E-Commerce in Indonesia has positioned Shopee as one of the most popular marketplaces. Consumers are increasingly considering product quality and price perception in their purchasing decisions. This study aims to analyze the extent to which product quality and price perception influence purchasing decisions on Shopee. Using a quantitative approach, this study collected data from respondents in North Bekasi. The findings indicate that product quality and price perception significantly affect purchasing decisions. Therefore, marketers must ensure high product standards and competitive pricing strategies to enhance customer loyalty.